A Note on Strongly Summable and Statistical Convergence Sequences of Fuzzy Numbers (Global Journal of Science Frontier Research, 2012)
In this article, we define and study the concepts of strongly - summable and - statistical convergence of sequence of fuzzy numbers for several relations among them.
Keywords: Sequence of fuzzy numbers; Difference sequence; Statistical convergence; Summability